Bonapartism: Loewenstein’s Essay Style and Method, and His Emphasis on ‘Going beyond Fact’ - Svátek, František (Dějiny – teorie – kritika, 2009)
The author follows on from his own overall description of Loewenstein’s historical thought, which he formulated ten years ago and called ‘crossing boundaries’. He now focuses on one of the dominant themes of Loewenstein’s research into the sources of Modernity in the nineteenth century – namely, the topic of ‘Bonapartism’, which is strikingly reflected also in the new book, Víra v pokrok (Faith in Progress). He traces how the topic gradually appeared in Loewenstein’s works in the early years of the re-establishment of a hard-line Communist regime (with its policy of ‘normalization’), which in turn had an innovative effect on samizdat history writing. The author also adds his own reflections on how his generation surmounted dogmatic Marxism.